PENGARUH RELATIONSHIP QUALITY TERHADAP CUSTOMER LOYALTY MELALUI CUSTOMER SATISFACTION PADA PERUSAHAAN JASA PT. POS INDONESIA DI SURABAYA - Natalia, Indahwati Christian (Kajian Ilmiah Mahasiswa Manajemen, 2013)
This study aimed to analyze the effect of relationship quality on customer loyalty through customer satisfaction at PT. Pos Indonesia in Surabaya. This study also aims to analyze the effect of relationship quality on customer loyalty and analyze customer satisfaction mediates the relationship to relationship quality on customer loyalty at PT. Pos Indonesia in Surabaya. The sampling technique used in this study is the purposive sampling technique. Determination of the respondents in this study were those who had used the services of PT. Pos Indonesia to the characteristics of 17- 60 years old who live in the city of Surabaya. Data analysis techniques used in this study is structural equation model (SEM).Results of this study indicate that there is positive between relationship quality on customer satisfaction and customer loyalty. Customer satisfaction has a positive effect on customer loyalty. And the results of this study also indicate relationship quality has a positive effect on customer loyalty through customer satisfaction.